PERAN PENDIDIKAN AGAMA ISLAM DALAM MENDORONG KESETARAAN GENDER TERHADAP PEREMPUAN DI DALAM ORGANISASI KEAGAMAAN IPPNU - Nur Khafidloh; Ahmad Saefudin (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2026)
This article examines the role of Islamic Religious Education in building an understanding of gender equality from the perspective of women involved in the Nahdlatul Ulama Female Student Association (IPPNU) religious organization, and identifies IPPNU's contribution to increasing women's participation in religious organizational spaces. This study aims to examine how theconcept of gender equality is understood and internalized by IPPNU women, and how the organization plays a role in encouraging women's involvement in leadership and socio-religious activities. The study used a qualitative approach with a case study design. Data collection techniques were carried out through interviews, observations, and documentation of IPPNU administrators and members. The results show that Islamic Religious Education delivered in a contextual and gender-equitable manner plays a role in shaping women's awareness of their rights, roles, and leadership capacity. IPPNU functions as a strategic non-formal educational space in fostering women's self-confidence, active participation, and substantive involvement in decisionmaking within religiousorganizations. However, the implementation of gender equality still faces cultural and social challenges. Therefore, strengthening the perspective of gender equality in Islamic Religious Education is crucial to encourage more equitable and sustainable women'sparticipation in religious organizations. Keywords : Islamic religious education, gender equality, women's emancipation, religious organizations,IPPNU.